El mal uso de las pensiones alimenticias efectuadas por el administrador puede representar una causal suficiente para privar de la tenencia del hijo o hija del progenitor quien la posee - Ordoñez Cordova, Christian Paúl (2022)
This Curriculum or Degree Integration Work is entitled: "THE MISUSE OF FOOD ALLOWANCES MADE BY THE ADMINISTRATOR CAN REPRESENT A SUFFICIENT CAUSE TO DEPRIVE THE POSSESSION OF THE SON OR DAUGHTER OF THE PARENT WHO POSSESSES IT" and aims to establish and structure a mechanism that allows the control in the expense of alimony to guarantee full and adequate access to the right to food closely related to the right to life, survival and integral development, in this work the qualitative and quantitative paradigm was used due to the fact that the right to food has been reviewed from a perspective of its basic qualities based on the contemporary reality of Ecuador and also its logical and doctrinal foundations have been revised in a prudent manner, which has allowed mechanizing the best alternative to the raised problem. Likewise, key figures in the protection of the rights of children and adolescents who are lawyers in free professional practice were interviewed to capture all the scientific and empirical information they can provide on the subject raised. Likewise, a survey and an interview have been carried out, which has allowed us to understand the public discernment on the right to food. It has been determined what the right to food consists of and how it works in Ecuador, in addition to its importance and its clear relationship with the right to life, survival and development, in clear accordance with the Doctrine of Integral Protection. It is established that the inappropriate use of alimony constitutes an act of violation of the rights of fed children and adolescents. The proposed proposal is necessary for the protection of the rights of children and adolescents, because it mechanizes a procedure that allows to better guarantee adequate access to the right to food in Ecuador.